Optimization of the Mechanical Properties of Bio-degradable Plastics from Chitosan with Acetic Acid Solvent - Purwanti, Ani; Sulistyaningsih, Eka; Prayogo, Wisnu; Yusuf, Muhammad (International Journal of Marine Engineering Innovation and Research, 2025)
Shrimp shell waste contains chitin which can be processed into chitosan. Chitosan can be utilized as an edible plastic. The film is expected to maintain food quality by resisting water vapour transfer as a preservative and maintaining odour. Edible plastics as food protectors are expected to have optimal mechanical properties. Chitosan films are brittle, so plasticizers are used to increase their flexibility. The mechanical properties of the film may change during storage time. The decline in film quality is expected to be fast enough to allow edible plastics for food wrapping. This study aims to determine the effect of glycerol addition and film storage time on the mechanical properties of edible chitosan film. From the results obtained, adding glycerol plasticizer produces films with thickness and elongation that tend to increase. In contrast, the tensile strength value increases and then decreases with the addition of glycerol. The optimal mechanical strength value was obtained in the film solution with glycerol at 0.3 mL/g chitosan with a maximum tensile strength of 200 kgf/cm2 and a per cent elongation of 135%. The thickness of the film produced was 0.17 mm. The film produced in this study has met the standards of film mechanical strength (tensile strength and per cent elongation) based on the Japanese Industrial Standard (JIS). Meanwhile, based on the Indonesian National Standard (SNI), the tensile strength value produced in this study has yet to meet the SNI standard.